Connection Quality Health Services With Neonatal Visits at the Community Health Center Tawangmangu and Karangpandan Karanganyar Regency - Dia Amana Saputri; Kusuma Estu Werdani (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Neonatal services are one of the government's efforts to reduce the risk of infant and maternal mortality. The quality of neonatal services is necessary to ensure that established standards provide services. The quality of neonatal services is related to postpartum mothers' compliance in carrying out neonatal visits. As primary health service providers, community health centers are responsible for providing optimal neonatal services. This study aims to determine the relationship between service quality and neonatal visits at Tawangmangu Health Center and Karangpandan Health Center, Karanganyar Regency. This research is a quantitative analytical research with a cross-sectional research design. The population in this study was postpartum mothers, totaling 119 people. The sampling technique is total sampling. The research sample was 112. The research instrument was a questionnaire. Data analysis uses the Chi-Square Test. The results of the study showed that there was no relationship between the quality of health services and neonatal visits at the Tawangmangu Health Center and Karangpandan Health Center, Karanganyar Regency (p-value 0.266; α > 0.005). Therefore, the quality of health services needs to be improved, especially in the dimension of empathy which is still lacking. Empathy can be enhanced through personal relationships with patients. Health workers should always provide information about the importance of visits to health services and also recommend involving the people closest to them so that mothers make regular visits to maintain their health and know the growth and development of babies and toddlers so that it can increase the mortality rate. speed. speed. Keywords: Quality of Service, Neonatal Visits, Community Health Center